2010
DOI: 10.1083/jcb.200912096
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA control of podosome formation in vascular smooth muscle cells in vivo and in vitro

Abstract: PDGF enhances podosome formation and cell migration by regulating expression of the microRNAs miR-143 and -145, which target PDGF-R, PKC-ε, and fascin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
159
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(171 citation statements)
references
References 44 publications
10
159
0
2
Order By: Relevance
“…Similarly, fascin-depletion altered colon carcinoma cell protrusion morphology, and decreased (i) the numbers of filopodia, (ii) Rac-dependent migration on laminin, (iii) turnover of focal adhesions and (iv) tumor development and metastasis in vivo (Hashimoto et al, 2007). In accordance with the cytoskeletal restructuring demonstrated by our study, miR-145-dependent regulation of fascin expression was suggested to modulate podosome formation in vascular smooth muscle cells (Quintavalle et al, 2010), with implications for the regulation of cell motility.…”
Section: Jam-a Is a Direct Target Of Transcriptional Regulation By MIsupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly, fascin-depletion altered colon carcinoma cell protrusion morphology, and decreased (i) the numbers of filopodia, (ii) Rac-dependent migration on laminin, (iii) turnover of focal adhesions and (iv) tumor development and metastasis in vivo (Hashimoto et al, 2007). In accordance with the cytoskeletal restructuring demonstrated by our study, miR-145-dependent regulation of fascin expression was suggested to modulate podosome formation in vascular smooth muscle cells (Quintavalle et al, 2010), with implications for the regulation of cell motility.…”
Section: Jam-a Is a Direct Target Of Transcriptional Regulation By MIsupporting
confidence: 69%
“…In addition to JAM-A, miR-145-dependent regulation of fascin may have contributed to the migratory phenotype. Fascin bundles lamellopodial actin filaments into filopodia (Hashimoto et al, 2007), and is a direct target of miR-145 in bladder cancer, esophageal squamous cell carcinoma and 3T3 cells (Chiyomaru et al, 2010;Kano et al, 2010;Quintavalle et al, 2010). Increased fascin expression enhances, and decreased expression reduces cell motility in esophageal squamous cell, gastric, prostate and colorectal cancer (Vignjevic et al, 2007;Darnel et al, 2009;Kim et al, 2009b;Qualtrough et al, 2009;Kano et al, 2010), and correlates with metastasis (Darnel et al, 2009).…”
Section: Jam-a Is a Direct Target Of Transcriptional Regulation By MImentioning
confidence: 99%
“…28,[30][31][32][33] Collectively, these findings indicate that fascin-1 functionally The molecular mechanisms of transcriptional regulation of fascin-1 have not been fully elucidated; however, the cAMP response elementbinding protein and aryl hydrocarbon receptor are candidate-positive regulators that enhance the promoter activity of fascin-1. 23,34 In contrast, several miRNAs, such as miR-133a, 133b, 143 and 145, are thought to negatively regulate the fascin-1 transcript in vascular smooth muscle cells 35 and carcinoma cells including urothelial carcinoma cells and squamous cell carcinoma cells. 18,36 These miRNAs have conserved sequences in the 3 0 untranslated region of fascin-1.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of experimental evidence has strongly supported that miRNAs are a critical regulator in controlling processes that underlie cell proliferation, differentiation and apoptosis in diverse organisms during normal development (Hassan et al 2012;Zhang et al 2013;Yang et al 2014). MiR-143, which was originally detected during adipocyte differentiation (Esau et al 2004), in many studies has emerged as an essential regulator of cellular physiology, particularly in tumorigenesis and cancer (Akao et al 2009;Quintavalle et al 2010;Qian et al 2013). In addition, recent studies show that miR-143 regulates the vascular smooth muscle cell phenotype (Boucher et al 2011).…”
Section: Discussionmentioning
confidence: 99%